Pawła Lubienieckiego obrona Biblii wobec „filozofów teraźniejszego wieku” .......... 203 - Dąbrowski, Roman (Przybylski i inni : nowe studia o znaczeniu Krakowa i regionu w kulturze oświecenia. Cz. 2, 2020)
PAWEŁ LUBIENIECKI’S DEFENCE OF THE BIBLE AGAINST “PHILOSOPHERS OF THE PRESENT AGE”The aim of the article is to show how Paweł Lubieniecki in the book The criticisms and accusations of the philosophers of the present age against faith … attempts to prove the validity of Christian dogmas by engaging in polemics with the deistic concepts of the Enlightenment. After briefly introducing the book and the author, attention is focused on the rhetorical aspect of his arguments. Lubieniecki’s views themselves, fully in line with Catholic doctrine, were assessed as not being particularly original. On the other hand, his striving to show that revealed truths are not only compatible with reason, but also may be rationally justified, has been emphasized. Hence, attention is focused on the excerpts of the book relevant to this issue, with attention focused on the quoted opinions of authorities: apart from the Bible, also the views of St. Augustine or Jean Jacques Rousseau.